(untitled) (Global Journal of Science Frontier Research, 2016)
It is shown that various natural phenomena, such as tsunamis, sound of church bells, resonance, etc., prove physical reality of imaginary numbers by the very fact of their existence and thereby refute the standard interpretation of the second STR postulate. Therefore, it is concluded that a common version of the special theory of relativity requires adjustment. The article represents analysis of possible structures of the hidden Multiverse corresponding to the adjusted version of the special theory of relativity, which explain the phenomena of dark matter and dark energy. It is shown that according to the data obtained by the WMAP and Planck spacecrafts, quaternion structure of the hidden Multiverse is the most probable.